An Analysis of Classical Arabic Teaching Methods in the Study of Classical Islamic Texts: A Case Study at an Islamic Boarding School - Muhammad Dzikron Maghfur; Ashfa Khoirun Nisa’; Daimah; Mowafg Masuwd (Assuthur: Jurnal Pendidikan Bahasa Arab, 2026)
Arabic language learning using classical methods is part of the tradition of studying kitab kuning through sorogan and bandongan. This method preserves the integrity of the chain of knowledge transmission from teacher to santri. The challenges of modernization demand more adaptive and efficient methods; however, the classical approach remains superior in maintaining the depth of textual understanding and the validity of knowledge. This study aims to analyze the implementation of classical Arabic learning methods in understanding kitab kuning at Pondok Pesantren Assalafiyah Purworejo, identify supporting and inhibiting factors, and examine the urgency and relevance of these methods in the contemporary era. This research employs a qualitative approach with a descriptive-analytical model based on field study. The results show that learning is carried out through a complementary combination of sorogan and bandongan, where sorogan emphasizes the readiness and responsibility of santri, while bandongan provides a basic understanding collectively. The continuity of the method is supported by the authority of the kiai, a structured learning environment, and the readiness of santri, but is constrained by limited time, the quality of instructors, and differences in santri ability. The urgency of this method lies in its ability to maintain the accuracy of text comprehension as well as the continuity of the pesantren’s scholarly tradition.